Barriers to Electric Car Acceptance: Analysis of Consumer Perceptions Regarding Safety and Security - Dwipayana, Arif Devi; Pradana, Adrian; Sulistyo, Aris Budi (ASTONJADRO, 2023)
The Indonesian government has issued Presidential Regulation Number 55 of 2019 concerning the acceleration of the battery-based electric motorized vehicle program. In 2019 the sales data for PHEV were 25 units and HEV was 787 units, sales of new BEV battery-based cars were recorded in 2020 totaling 125 units, PHEV and HEV were sold 8 and 1,191 units. For 2021 sales of BEV were 687 units, PHEV 46 units and HEV 2,472 units and until March 2022, BEV sales were 64 units, PHEV 10 units and HEV 646 units. It can be seen from the above data that sales growth has occurred, but it is still quite low compared to fossil fuel cars (a percentage of no more than 0.5% each year). Seeing the number that is still minimal, it is necessary to look at the obstacles that occur in the community, why this can happen, even though the Indonesian government wants to build an integrated electric vehicle ecosystem to encourage energy security and domestic energy independence so as to reduce dependence on the use of fuel oil and reduce greenhouse gas emissions. One of these obstacles is the aspect of safety and security. The survey was conducted throughout the provinces of Indonesia with the results that the most perceived obstacles from the aspect of safety and security were batteries, very minimal sound noise, geographical and weather conditions in Indonesia and the risk of hacking, ransomware and other forms of cyber attacks due to sophisticated technology. attached to an electric car. Another result that is in the spotlight is that there are still many respondents who answered they did not know about electric cars,